Pengaruh Emosi Positif Guru SLB-C terhadap Sikap Anak Tunagrahita di SLB Negeri 1 Badung - Sagung Putri Permana Lestari Murdhana Putere; Rima Kusuma Ningrum; Putu Erna Maharani (Aesculapius Medical Journal, 2022)
Positive emotions are emotions that can bring positive feelings to someone who experiences them. The purpose of this study was to determine the effect of the positive emotional role of SLB-C teachers on the attitudes of mentally retarded children in SLB Negeri 1 Badung. This study was designed using a qualitative approach. The sample used in this study were five respondents from SLB Negeri 1 Badung teachers and five respondents from parents of mentally retarded children who attended SLB Negeri 1 Badung. In this data collection using interview and observation methods and, the selected informants are communicative and willing to provide information. Furthermore, the analysis of interview data with interactive analysis, in this analysis is carried out interactively and continues until the data is saturated. The steps in this analysis are making interview transcripts, analyzing data in the form of coding, describing the results of the data in the form of narration and interpreting the data. The results of this study indicate that positive emotions affect the attitude of mentally retarded children from the point of view of parents revealing that their children are no longer hyperactive and can carry out activities independently while at home and at school. In addition, the effect of applying teaching with positive emotions such as a happy attitude, patience, sincerity, affection and attention has an impact on mentally retarded children. The influence is that the environmental conditions during class are more conducive and mentally retarded children can feel more comfortable and calm and can communicate with their teachers, this communication can be seen from the teacher's questions and answers to students.